2022
DOI: 10.3390/su14148604
|View full text |Cite
|
Sign up to set email alerts
|

Do an Organization’s Digital Transformation and Employees’ Digital Competence Catalyze the Use of Telepresence?

Abstract: Rapid changes in the external environment are increasing interest in digital transformation. In particular, the recent breakout of infectious diseases such as COVID-19 has required certain companies to restrict physical exchanges among their members. As a result, companies must strive to maintain productivity and performance by supporting business exchange activities through online platforms. A metaverse technology that supports individuals’ exchange activities in a virtual space based on 3D technology has rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…This phenomenon implies that tele-pre-sence enhances the authenticity of live streaming, effectively immersing consumers in the world crafted by streamers (Gao et al, 2021). The results of research conducted by (Hwang et al, 2022) show that telepresence influences motivation of use leading to enjoyment in metaverse world. Thus, it can be concluded that H1: Telepresence has a positive effect on enjoyment…”
Section: The Effect Of Telepresence On Enjoymentmentioning
confidence: 97%
“…This phenomenon implies that tele-pre-sence enhances the authenticity of live streaming, effectively immersing consumers in the world crafted by streamers (Gao et al, 2021). The results of research conducted by (Hwang et al, 2022) show that telepresence influences motivation of use leading to enjoyment in metaverse world. Thus, it can be concluded that H1: Telepresence has a positive effect on enjoyment…”
Section: The Effect Of Telepresence On Enjoymentmentioning
confidence: 97%
“…e) Visit to companies and organizations: In the metaverse, companies and organizations can be recreated so that students can learn about different sectors of the economy and explore employment and entrepreneurship opportunities (Hwang, Shim & Lee, 2022).…”
Section: D) Visit To Universities and Research Centersmentioning
confidence: 99%
“…The organizations will have to motivate and engage the employees in learning and enhancing their digital capabilities, which will, in turn, help in employee retention. In addition, organizations will have to conceptualize their digital transformation policies to ascertain the business use of metaverse within their organization and also ensure the involvement of employees in the new policy by communicating the organizational goals and values to them (Hwang et al, 2022). It is interesting to note that the metaverse itself can be adopted as a training ecosystem and can be used for providing immersive training which may be beneficial for both the employees and organizations (Upadhyay, Khandelwal, 2022).…”
Section: Theme 3 -Human-resource-related Aspectsmentioning
confidence: 99%